1998
DOI: 10.1289/ehp.9810623
|View full text |Cite
|
Sign up to set email alerts
|

Relative potency of xenobiotic estrogens in an acute in vivo mammalian assay.

Abstract: The in vii effcts ofxenoestrogens are ofinterest in relation to their potential health risk and/or beneficial efficts on humans and animals. However, the apparent in yim potency of the examined response can be confounded by a short half-ife, and the metabolism of estogens is very dependent on the nature of conversion and/or inactivation. To minimize such variables, we examined the estrogenic potency of a range of xenoestrogens in an acute in vivo assay-the stimulation of increased uterine vascular permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(73 citation statements)
references
References 20 publications
6
65
2
Order By: Relevance
“…In addition to compounds naturally occurring in plants and some mycotoxins (Breithofer et al 1998;Miksicek 1994), various pesticides and industrial chemicals have shown estrogenic effects in vitro (Jobling et al 1995;Klotz et al 1996;Körner et al 1998;Miller et al 2001;Soto et al 1991;Soto et al 1995) and in vivo in mammals (Dodds and Lawson 1936;Milligan et al 1998;Nagel et al 1997;Soto et al 1991) as well as fish (Christiansen et al 2000;Donohoe and Curtis 1996;Gimeno et al 1996;Jobling et al 1996). However, we have not identified a common chemical substructure responsible for the estrogenic activity of the so-called xenoestrogens and phytoestrogens.…”
mentioning
confidence: 72%
“…In addition to compounds naturally occurring in plants and some mycotoxins (Breithofer et al 1998;Miksicek 1994), various pesticides and industrial chemicals have shown estrogenic effects in vitro (Jobling et al 1995;Klotz et al 1996;Körner et al 1998;Miller et al 2001;Soto et al 1991;Soto et al 1995) and in vivo in mammals (Dodds and Lawson 1936;Milligan et al 1998;Nagel et al 1997;Soto et al 1991) as well as fish (Christiansen et al 2000;Donohoe and Curtis 1996;Gimeno et al 1996;Jobling et al 1996). However, we have not identified a common chemical substructure responsible for the estrogenic activity of the so-called xenoestrogens and phytoestrogens.…”
mentioning
confidence: 72%
“…1-10 mM, in agreement with their significant estrogenic activity when present in very large quantity. In vivo, BPA increases VEGF expression in the immature rat uterus (37 mg/kg being the lowest active dose; Long et al 2001); genistein, BPA, OP, and BBP have also been shown to increase uterine vascular permeability in ovariectomized mice (Milligan et al 1998); no evidence of any significant synergy or antagonism between the compounds were observed (Milligan et al 1998), in agreement with our data showing that low doses of xenoestrogens (i.e., below the level required to induce an estrogenic response) were ineffective in combination with a stimulatory dose of E 2 (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic rodent studies, several of the phthalates produced testicular injury, liver injury, liver cancer, and teratogenicity, but these effects either have not been demonstrated when tested in non-human primates or are yet to be studied. In vitro studies showed that certain phthalates can bind to estrogen receptors and may have weak estrogenic or anti-estrogenic activity (Coldham et al, 1997;Harris et al, 1997;Jobling et al, 1995), but in vivo studies did not support phthalates having estrogenic effects (Milligan et al, 1998;Okubo et al, 2003;Parks et al, 2000;Zacharewski et al, 1998); however, not all phthalates…”
Section: Phthalates General Informationmentioning
confidence: 99%